General framework and modeling approach classification for chemical production scheduling - Maravelias, Christos T. (AIChE journal, 2012)
Despite the increased number of publications in the area during the last two decades, there is no unified notation and systematic framework for chemical production scheduling. In this article, we first develop a framework for the description of scheduling problems in the chemical industries. While building upon ideas used in discrete manufacturing, the proposed framework accounts for features such as material handling restrictions which are critical in chemical production scheduling. Second, we present a classification of the various modeling approaches that have been presented in the process systems engineering literature. Our classification is broader than previous schemes because it accounts for more attributes, and it also offers a broader discussion of the modeling of time. We believe that our analysis will enhance the understanding of chemical production scheduling and lead to further advances in the area. © 2012 American Institute of Chemical Engineers AIChE J, 58: 1812–1828, 2012